An Analysis of Teachers’ Strategies Scaffolding In EFL Reading Class - Tria Khaerunisa; Putri Kamalia; Evi Karlina Ambarwati; Nina Puspitaloka; Indah Purnama Dewi (Publikasi Indonesia, 2026)
This study analyzes the scaffolding strategies employed by EFL (English as a Foreign Language) teachers in teaching reading comprehension to secondary school students. The research aims to evaluate the effectiveness of these strategies in addressing the challenges faced by students in understanding narrative texts. A qualitative case study approach was adopted, involving observations, interviews, and documentation methods to gather data from seventh-grade students at SMPN 1 Cilamaya Wetan. The findings indicate that while the scaffolding strategies applied generally align with the principles of effective reading instruction, there are areas for improvement in both the narrative texts used and the implementation of these strategies. This research contributes to the understanding of how scaffolding can enhance reading comprehension and offers recommendations for educators to refine their teaching practices.